Wildlife Conservation, Management and Disease Surveillance - Sharma, A. K.; Saini, Mohini; Das, Asit (Indian Farming, 2015)
The Centre for Wildlife Conservation, Management and Disease Surveillance was established in 1984. Significant research activities are ongoing at the Centre since its inception. The Centre has been able to provide disease diagnostic facilities and wildlife health management consultancy, besides conducting research on need based problems in wildlife.